Economic Openness: A Key Success or a Threat to Economic Growth in Indonesia for the Period 1988-2022? And How Does It Relate to the Development of Agribusiness? - Hartini, Hartini; Aulia, Muhammad Reza; Nasution, Anisah (Universitas Galuh, 2024)
Economic openness is an important pillar in the current era of globalization in encouraging a country's economic growth. This study aims to analyze how much influence economic openness has on economic growth with control variables in the form of foreign investment (FDI) and Inflation in Indonesia for the period 1988-2022. This research method uses multiple linear regression analysis with Eviews 10 analysis tool. The results showed that economic openness and foreign investment have a positive and significant effect on economic growth, while inflation has a negative and significant effect on economic growth in Indonesia. The results of this study are expected to provide an in-depth understanding of the effect of economic openness on economic growth and relevant data for policy makers to make better, strategic and more effective decisions in supporting sustainable and inclusive economic growth in the country of Indonesia. Indonesian government has undertaken a series of proactive measures, including expanding market access, imparting advanced agricultural techniques to farmers, and investing in agricultural infrastructure. These initiatives have become instrumental in driving the economic development of agriculture and the expansion of agribusiness.Keywords: agribusiness development, economic growth, foreign direct investment, inflation, trade openness